KEPUTUSAN PEMBELIAN E-COMMERCE SHOPEE DITINJAU DARI KUALITAS PRODUK, PERSEPSI RESIKO, DAN KEPERCAYAAN (STUDI PADA MAHASISWA UNIVERSITAS ISLAM BATIK SURAKARTA) - Refris Ridha Zaindhika; Burhanudin Ahmad Yani; Fithri Marwati (JURNAL ILMIAH EDUNOMIKA, 2020)
The purpose of this study was to determine whether there is a significant influence between variables of product quality, risk perception, and trust on shopee e-commerce purchasing decisions. In addition, it is also to find out whether there is a significant simultaneous influence and which variable is the most dominant in influencing shopee e-commerce purchasing decisions on students of the Islamic University of Batik Surakarta. The method used is descriptive quantitative method. The population in this study amounted to 2,797 students and the sample used was 100, where the sampling technique used accidental sampling. The data used are primary data and secondary data with data collection techniques: observation, documentation, questionnaire and literature study. The data analysis technique in this study used multiple linear tests. The results of the study can be concluded that: The results of the study can be concluded that: 1) There is an effect of product quality, risk perception, and trust have a simultaneous effect on purchasing decisions of e-commerce shopee on students of the Islamic University of Batik Surakarta, 2) There is an effect of product quality on purchasing decisions e-commerce shopee for students of the Islamic University of Batik Surakarta, 3) There is an effect of risk perception on shopee ecommerce purchasing decisions for students of the Islamic University of Batik Surakarta, 4) There is an effect of trust on shopee e-commerce purchasing decisions for students of the Islamic University of Batik Surakarta. Keywords: Purchasing Decisions, Website Quality, Product Innovation, Electronic Word Of Mouth